2011
DOI: 10.2337/dc10-2221
|View full text |Cite
|
Sign up to set email alerts
|

A Pregnancy and Postpartum Lifestyle Intervention in Women With Gestational Diabetes Mellitus Reduces Diabetes Risk Factors

Abstract: OBJECTIVETo pilot, among women with gestational diabetes mellitus (GDM), the feasibility of a prenatal/postpartum intervention to modify diet and physical activity similar to the Diabetes Prevention Program. The intervention was delivered by telephone, and support for breastfeeding was addressed.RESEARCH DESIGN AND METHODSThe goal was to help women return to their prepregnancy weight, if it was normal, or achieve a 5% reduction from prepregnancy weight if overweight. Eligible participants were identified short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
237
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(254 citation statements)
references
References 17 publications
10
237
2
5
Order By: Relevance
“…Our data indicate that this association may partly be explained by the lower weight loss post-partum and not so much by the diagnosis of GDM itself. In a pilot randomized trial, Ferrara et al (36) have recently reported that GDM women receiving prenatal/post-partum intervention to modify diet and physical activity show a higher probability of reaching post-partum weight goal (defined as prepregnancy weight if BMI !25 kg/m 2 and K5% of prepregnancy weight if BMI O25 kg/m 2 ) 12 months post-partum. The associations among maternal weight changes, HbA1c levels in PCOS women, GDM, type 2 diabetes, and later cardiovascular disease should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that this association may partly be explained by the lower weight loss post-partum and not so much by the diagnosis of GDM itself. In a pilot randomized trial, Ferrara et al (36) have recently reported that GDM women receiving prenatal/post-partum intervention to modify diet and physical activity show a higher probability of reaching post-partum weight goal (defined as prepregnancy weight if BMI !25 kg/m 2 and K5% of prepregnancy weight if BMI O25 kg/m 2 ) 12 months post-partum. The associations among maternal weight changes, HbA1c levels in PCOS women, GDM, type 2 diabetes, and later cardiovascular disease should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of community-based DPP translations have shown promising results over relatively short time frames [11,12]. However, limited efforts have been made to translate the DPP for women with a history of GDM [13,14], especially those with low socioeconomic status (SES). This represents a critically missed opportunity [15] given that a GDM diagnosis identifies individuals at a very high risk for future T2DM [1,16] and that lifestyle intervention is an effective diabetes prevention strategy for women with history of GDM [16].…”
Section: Introductionmentioning
confidence: 99%
“…8 Lifestyle interventions are a successful means of preventing T2D in high-risk individuals for T2D; 9,10 the effectiveness of lifestyle intervention in women with a history of GDM have also been examined to some extent. [11][12][13][14][15][16][17] In the Tianjin Gestational Diabetes Mellitus Prevention Program, lifestyle intervention yielded beneficial changes in weight, body mass index (BMI), body fat, waist circumference, plasma insulin levels, physical activity and diet in women with prior GDM during the 1-year follow-up. 17 Other studies have also shown that lifestyle intervention reduced weight and BMI, 13,16 and yielded beneficial changes in diet 15,16 and leisure time physical activity 16 in women with GDM.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] In the Tianjin Gestational Diabetes Mellitus Prevention Program, lifestyle intervention yielded beneficial changes in weight, body mass index (BMI), body fat, waist circumference, plasma insulin levels, physical activity and diet in women with prior GDM during the 1-year follow-up. 17 Other studies have also shown that lifestyle intervention reduced weight and BMI, 13,16 and yielded beneficial changes in diet 15,16 and leisure time physical activity 16 in women with GDM. In addition, in the Diabetes Prevention Program (DPP), the effect of lifestyle intervention on T2D risk reduction was similar in women with and without a history of GDM, but women without GDM lost more weight during the follow-up.…”
Section: Introductionmentioning
confidence: 99%